Effects on Self-Esteem, Interpersonal Relations Ability and Job Stress In Apartment House Private Security Guards - Kim, Ja-Ok; Park, A Young; Kim, Hyun-Suk; Park, Hae-Ryoung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to provide basic data for policy development to improve health promotion and self-esteem of apartment house private security guards. This study is to investigate the degree of job stress, interpersonal ability and self-esteem of apartment house private security guards. Methods/Statistical analysis: The subjects were 97 apartment house private security guards at G city. The research method was used by citing 24 short items of Korean job stress measurement tool, and the interpersonal relationship ability tool was used by Performance Solution International (PSI). A four-point scale with 10 items was used to measure self-esteem. The analysis of differences in job stress, interpersonal relationship ability and self-esteem was analyzed by independent t-test and one-way ANOVA. The correlation between job stress, interpersonal relationship ability and self-esteem was analyzed by Pearson’s correlation. Findings: Age of the subjects, 60 people were younger than 70 years of age (61.9%), and 42 people were 70 or older (38.1%), and the mean age was 68.2±4.9. There was a statistically significant difference in the job stress of the subjects between age (t = 2.0 p = .049), presence of restructuring (t = 2.83, p = .006), presence of exercise (t = -2.52, p = .013) there was. There was a statistically significant difference in the ability of interpersonal relationship ability among the subjects with and without smoking (t = -2.03, p = .045). The self- esteem of the subjects was statistically significant at the level of education (F = 3.27, p = .042). The subjects’ job stress and interpersonal relationship ability (r = -. 206, p = .043) showed a negative correlation. Interpersonal relationship ability and self-esteem (r = .554, p <.001) showed a significant positive correlation. The higher the job stress, the lower the interpersonal relationship abilities and the higher the interpersonal relationship abilities, the higher the self-esteem. Improvements/Applications: Based on the results of this study, the basic data for enhancing health promotion and self-esteem of apartment house private security guards. The purpose of this study is to present basic data for the development of mediation programs and policies to reduce job stress and improve interpersonal relationship ability and self-esteem.